Demographic characteristics of children with early clinical manifestation of inflammatory bowel disease - Szymańska, Edyta; Szymańska, Sylwia; Szczepański, Michał; Landowski, Piotr; Czaja-Bulsa, Grażyna; Jarocka-Cyrta, Elżbieta; Korczowski, Bartosz; Krzesiek, Elżbieta; Kierkuś, Jarosław (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Inflammatory bowel disease (IBD), which includes Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic condition of the colon and small intestine. The disease is common in young people (children and young adults), but it is rare in children younger than five years of age. Therefore, IBD developing during the first years of life (under the age of 5) is known as an early-onset IBD (EO-IBD), and it is considered to be a specific entity with a distinct phenotype. However, the available data on that issue are still insufficient. Aim: To determine the characteristics and clinical course of children with early-onset IBD. Material and methods: We performed a retrospective database analysis of 47 infants younger than 5 years old diagnosed with IBD. Patient’s demographic data, including age, sex, and age at disease onset, were collected in 6 paediatric hospitals in Poland. Disease location was established on the basis of the review of all endoscopic, colonoscopic, histopathological, and radiological records. All possible complications were reported, as well as any treatment and its efficacy. Since the diagnosis was established all patients have been on follow up. Results : Among 47 children registered in the database, 23 (49%) had a diagnosis of CD, 16 (34%) had UC, and 8 (17%) had IC (indeterminate colitis). The mean age at diagnosis was 28.5 ±27.5 months; 57.4% were male. The most common location/type of disease was ileocolonic disease (L3). The most common complication of IBD was anaemia, found in 30 (63.8%) children. The observed course of the disease was either severe or moderate. In 4 children younger than 2 years old, surgery was performed. Conclusions : Inflammatory bowel disease in children younger than 5 years old includes UC, CD, and a relatively high proportion of IC. In early-onset IBD severe and moderate course of the disease is usually observed. Disease manifestation in these patients is predominantly ileocolonic.